The Transformation of Islamic Education Pedagogy: From Lecture-Dominated Teaching to Interactive Learning to Improve Student Concentration - Siti Nurhayati; Iqbal Amar Muzaki; Ferianto Ferianto (Journal of Indonesian Islamic Studies, 2026)
This study aims to analyze the pedagogical transformation of Islamic Religious Education (IRE) from the dominance of the lecture method toward interactive learning as an effort to improve student learning concentration at SMPIT Al-Ridwan. Previous studies have mostly discussed innovations in IRE learning methods, whereas research specifically linking the dominance of the lecture method to low student concentration and the pedagogical transformation toward interactive learning remains relatively limited. The study employed a descriptive qualitative approach conducted in 2026, involving one PAI teacher and 16 seventh-grade A students. Data were collected through observation, interviews, and documentation, then analyzed via data reduction, data presentation, and drawing conclusions. The results indicate that the dominance of the lecture method causes students to tend to be passive, easily bored, unfocused, and have low levels of participation. In response to these conditions, the teacher implemented interactive learning through group discussions, question-and-answer sessions, and audiovisual media, which encouraged more active student engagement. The findings reveal changes in learning behavior marked by increased attention, participation, and student engagement during the learning process. The novelty of this study lies in the analysis of the transformation of Islamic Education pedagogy from a teacher-centered approach to a student-centered approach as a strategy to address learning concentration issues. Theoretically, this study expands the discourse on Islamic Education pedagogy by demonstrating that students’ learning concentration is closely related to the pedagogical orientation applied by teachers in the learning process.